The role of stakeholders in Solomon’s Temple: An exploratory study - Bazanini, Roberto; Giglio, Ernesto Michelangelo (Organizações & Sociedade, 2017)
This paper aims to describe the role of stakeholders in the symbolic goods market of religion. Drawing on qualitative research, and based on the salience model of stakeholders, the objective is to analyze the importance of Solomon’s Temple megachurch to the Universal Church of the Kingdom of God (UCKG) as a competitive factor in the market of religious goods and services for achieving a competitive advantage. The findings show that the respondents’ perception indicates that the construction of megachurches provides a competitive advantage if the staNeholders are identifed and continuously monitored because of the attributes of power, legitimacy and urgency. The contribution of the study is a discussion on the relevance of the applicability of stakeholder theory in the symbolic goods market of religion from the perspective of network relationships with other stakeholders.